Reflections on Leadership: Theory, Experience, and Practice: National Association for Kinesiology in Higher Education 36th Dudley Allen Sargent Commemorative Lecture 2017. Issue 2 (3rd April 2017) - Germain, Jesse
ABSTRACT: This article, which was delivered as the Thirty-Sixth Annual Dudley Allen Sargent lecture at the 2017 conference of the National Association for Kinesiology in Higher Education (NAKHE), discusses transformational leadership theory as an effective approach to inspiring subordinates and creating a culture that results in a shared vision and common approach to a positive organizational future. Contrasting a transformational versus transactional approach, it uses both published papers and leadership reflections from many of NAKHE's most successful emerging and experienced professionals to provide suggestions on leadership methods that can be incorporated to facilitate transformative change.